The Growth of the Law in Medieval Russia - DANIEL H. KAISER (Princeton University Press, 2014)
Several observations are in order before introducing the reader to this book's argument. We may begin with definitions. This study is titled The Growth of the Law in Medieval Russia, and that alone may be enough to distress some of my colleagues. Please note that I have not labeled it The Evolution of the Law. I have no confidence that the law, or any other facet of culture, must move inevitably along some progressive continuum. On the contrary, anyone who has read the literature on sanctions must at least doubt the wisdom of contemporary notions of deterrence and criminal law. On the other hand, it seems to me that the law does grow as the informal constraints of traditional society recede, for whatever reason those constraints recede. The law's growth is not uniformly beneficial—in fact it need not be uniform at all. But, in general, larger societies with a more heterogeneous makeup demand a larger body of enunciated law for effective regulation of behavior. Scholars interested in modernization theory will have noticed that I introduced into the preceding paragraph a term now slighdy out of vogue. In recent years the whole idea of traditionalism has been much discussed, and I confess to having stumbled upon the debate unwittingly. Furthermore, I would very much like to stay out of it altogether. Nevertheless, I have employed the word and idea of traditionalism in these pages, and I offer here a few words in its defense. What I intend by tradition is that tendency "to accept the givenness of some past event, order or figure . . . as the major focus" of a society's collective identity, as S. N. Eisenstadt puts it. I realize that the simplicity of my construct hides the rich diversity of cultures. Indeed, what strikes my eye is precisely the fact that some societies feel no need to elaborate in detail their norms or the means for ensuring socially acceptable behavior. Consequently, I find very palatable Edward Shils's suggestion that we conceive of tradition as "society's reservoir of behavior and symbols." In medieval Russia it was that reservoir of symbols which resisted the introduction of new legal norms, not necessarily because the old were superior to the new, but simply because the old norms were old norms. Again I hasten to assure the reader that I do not intend to denote or connote by "tradition" some lesser state of civilization. Inasmuch as I subscribe to a pessimistic view of man, it is difficult for me to suppose that man is necessarily building over the course of time a qualitatively better society. As in most things, notions of quality vary with time and place, and I do not here propose a unilinear, infinite progression. That having been said, I find no persuasive reason to abandon the idea of traditionalism.